FUNdraising : 50 Proven Strategies for Successful School Fundraisers. - Sennett, Frank (SAGE Publications, 2007)
Presents 50 fun, creative, and cost-effective fundraising strategies from schools across the country and includes savvy organizing tips, guidance on ethical issues, and advice for avoiding mishaps.